The Mediaeval Background of Self-Identification in Relation to the Filioque Controversy - András, Szabolcs (Review of ecumenical studies, 2021)
The study at hand is not focused on the mediaeval theological history of the Filioque controversy but aims to examine how the mediaeval (particularly the Palamite) doctrine of procession has become an ideological element of identity in presentday interpretation. Based on the assumption that religious elements have become part of the political identity primarily in south-eastern Europe, the present paper makes reference first of all to representatives of Orthodox theology, without seeking to criticize, however, the Orthodox standpoint on the Filioque. Provided that it can be demonstrated that contemporary authors make use of mediaeval sources not merely theologically but also ideologically, then we can ascertain that the mediaeval Filioque controversy inşuences the present-day interpretation of self-identity.